2019
DOI: 10.3311/ppee.14379
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Coupling Reduction in Patch Antenna Array Based on EBG Structure for MIMO Applications

Abstract: This paper presents a printed rectangular slot microstrip antenna array of two elements based on an Electromagnetic Band Gap (EBG) structure. The proposed EBG structure is invented to improve the isolation between the radiating elements for multiple-input multiple-output (MIMO) application. Single and two slotted rectangular microstrip antennas are designed on an FR-4 substrate with a dielectric constant (εr) of 4.3 and loss tangent (tanδ) of 0.025 with thickness of 1.6 mm. The proposed EBG structure is design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…7 and 8), it is found that the folded antenna profile exhibits a shift in the frequency resonance from 5 GHz to 5.03 GHz. The frequency shift is attributed to the effects of patch bending that realizes surface current motion on a substrate [12]. The impedance matching is improved for the folded profile, and simultaneously, the realized gain is reduced without significant effects on antenna bandwidth compared to the planar profile as seen in Figs.…”
Section: Comparison Between the Planar And Folded Antenna Profilesmentioning
confidence: 98%
See 1 more Smart Citation
“…7 and 8), it is found that the folded antenna profile exhibits a shift in the frequency resonance from 5 GHz to 5.03 GHz. The frequency shift is attributed to the effects of patch bending that realizes surface current motion on a substrate [12]. The impedance matching is improved for the folded profile, and simultaneously, the realized gain is reduced without significant effects on antenna bandwidth compared to the planar profile as seen in Figs.…”
Section: Comparison Between the Planar And Folded Antenna Profilesmentioning
confidence: 98%
“…Therefore, the present wireless communication technology invoked tremendous interest in smart antennas, especially for 4G and 5G [10]. For this, the researchers have been attracted to utilize reconfigurable smart antennas to improve the wireless communication systems performance in different applications [11][12][13]. However, they faced a new challenge: integrating antennas with modern high-speed semiconductors while maintaining the size miniaturization and keeping high gain-bandwidth produce over the frequency band of interest [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, these antennas suffered from low and unstable gain performance. Therefore, the introduction of metamaterial structures to the antenna designs has become common because of their unique electromagnetic properties [8], such as low or zero refractive indexes which control the antenna radiation [9]. Abdul Hassain et al [10] introduced a microstrip antenna with zero refractive index metamaterials in the substrate, which improved the gain by 1 dB to 2 dB.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, etching the slit structures on the metal-frame can effectively solve this problem [15][16][17][18]. The application of new decoupling technologies and structures such as substrate integrated waveguide (SIW) and electromagnetic band gap (EBG) has greatly improved the isolation between adjacent antennas [19][20][21]. In recent years, some multi-band 5G MIMO antenna arrays have been reported for 5G mobile communications, while only a few can integrate metalframe as a vital component for the smartphones [22][23][24].…”
Section: Introductionmentioning
confidence: 99%